2017
DOI: 10.3390/molecules22040558
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Sulfur to Produce Allium Functional Crops

Abstract: Selenium is an element that must be considered in the nutrition of certain crops since its use allows the obtaining of biofortified crops with a positive impact on human health. The objective of this review is to present the information on the use of Se and S in the cultivation of plants of the genus Allium. The main proposal is to use Allium as specialist plants for biofortification with Se and S, considering the natural ability to accumulate both elements in different phytochemicals, which promotes the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 190 publications
(204 reference statements)
0
30
0
Order By: Relevance
“…On the other hand, AMF inoculation of several other agricultural crops, such as lettuce [90], maize, alfalfa, and soybean [91], reduced the Se content in plants. Similar controversies arose from studies focusing on AMF effect on accumulation of sulfur, which is a Se chemical analog [47,66,67,92].…”
Section: Selenium-amf Interactionmentioning
confidence: 96%
“…On the other hand, AMF inoculation of several other agricultural crops, such as lettuce [90], maize, alfalfa, and soybean [91], reduced the Se content in plants. Similar controversies arose from studies focusing on AMF effect on accumulation of sulfur, which is a Se chemical analog [47,66,67,92].…”
Section: Selenium-amf Interactionmentioning
confidence: 96%
“…Damaziak et al [116] indicated that administration of the dietary onion extract to hens resulted in heavier eggs, with a higher content of egg yolk and better quality of albumen. The genus Allium has an exceptional ability to absorb, metabolize, and store selenium as organoselenium compounds such as selenomethionine and selenocysteine [117]. Olobatoke and Mulugeta [67] had given the possible explanation to the increased egg weight in laying hens is the absorption of garlic compounds (selenomethionine and selenocysteine) and their subsequent deposition in the egg yolk.…”
Section: Effects On Product Qualitymentioning
confidence: 99%
“…Selenite presents a higher phytotoxicity when compared to selenate (Ríos et al, 2010;Guerrero et al, 2014;González-Morales et al, 2017). Therefore, an increase in carotenoid content was observed when foliar selenite was applied.…”
Section: Physical-chemical Characteristics and Carotenoid Contents Inmentioning
confidence: 99%